How Do We Improve Patient Compliance and Adherence to Long-Term Statin Therapy? - Maningat, Patricia (2013)
Statins are highly effective drugs prescribed to millions of people to lower LDL-cholesterol and decrease cardiovascular risk. The benefits of statin therapy seen in randomized clinical trials will only be replicated in real-life if patients adhere to the prescribed treatment regimen. But, about half of patients discontinue statin therapy within the first year, and adherence decreases with time. Patient, physician and healthcare system-related factors play a role in this problem. Recent studies have focused more on the patients’ perspectives on non-adherence. Adverse events are cited as the most common cause of statin discontinuation; thus, the healthcare provider must be willing to ally and dialogue with patients to address concerns and assess the risks and benefits of continued statin therapy.